Um mundo sem empregos ou de desemprego: relações possíveis entre homem e trabalho para o século XXI - Santos, Michelle Steiner dos (1999)
At the dawn of this century, scientists and common people passed questioning on the use and development every time larger of a practice, view until very little time behind with optimism, as the humanity's salvation, as the differentiation of our species and another animals, the scientific progress. Inquiries appeared from everywhere, but still with the same kind of work, workers and production system. The menace of the end of the employments and the progressive amount of sick people due to their jobs or in the lack of these, took and is taking researchers to investigate the impacts of the scientific evolution in the human relationships, in the constitution of new ways of noticing the man in its personal and professional universe. It can be noticed that the unemployment is taking the State to make its juridical systems and its laws, more flexible allowing the construction of new work relationships that on their turn constitute new identities. The terceirizações and more precisely the cooperatives, are fruit of that re-dimensioning process, of life and death, of human future in the end of century XX. The objective with this dissertation, is to demonstrate that although the perspective of a world without employments configures new relationships in the work contracts, these not always lead to a new way of thinking the worker and the man. The work cooperatives, are the largest examples of this fact. Although they are, for its own configuration, one of the most viable and flexible alternative, economically and socially speaking, for workers and managers faced to the market, they are used many times in an illicit way. Even so, nothing is lost; the man possesses the infinite capacity to change while identity and starting from its action, to transform the world. The ways exist; it is enough to travel them. A possible choice is the Ergonomics. It fits to the ergonomist on this new millennium, to change its profile, to adapt to the changes, to include new functions. One of these functions is without a doubt the organizational re-orientation of managers and workers.